Improved Cepstra Minimum-Mean-Square-Error Noise Reduction Algorithm For Robust Speech Recognition - Li, Jinyu; Huang, Yan; Gong, Yifan (ICASSP, 2017)
In the era of deep learning, although beam-forming multi-channel signal processing is still very helpful, it was reported that single-channel robust front-ends usually cannot benefit deep learning models because the layer-by-layer structure of deep learning models provides a feature extraction strategy that automatically derives powerful noise-resistant features from primitive raw data for senone classification. In this study, we show that the single-channel robust front-end is still very beneficial to deep learning modelling as long as it is well designed. We improve a robust front-end, cepstra minimum mean square error (CMMSE), by using more reliable voice activity detector, refined prior SNR estimation, better gain smoothing and two-stage processing. This new front-end, improved CMMSE (ICMMSE), is evaluated on the standard Aurora 2 and Chime 3 tasks, and a 3400 hour Microsoft Cortana digital assistant task using Gaussian mixture models, feed-forward deep neural networks, and long short-term memory recurrent neural networks, respectively. It is shown that ICMMSE is superior regardless of the underlying acoustic models and the scale of evaluation tasks, with 25.46% relative WER reduction on Aurora 2, up to 11.98% relative WER reduction on Chime 3, and up to 11.01% relative WER reduction on Cortana digital assistant task, respectively.